2011
DOI: 10.1007/s00253-011-3179-5
|View full text |Cite
|
Sign up to set email alerts
|

From shake flasks to bioreactors: survival of E. coli cells harboring pGST–hPTH through auto-induction by controlling initial content of yeast extract

Abstract: A high content of yeast extract in complex media can cause auto-induction of phage T7 RNA polymerase and the consequent expression of recombinant protein in Escherichia coli BL21(DE3) during long-term cultivation. Our study demonstrated that the auto-induction of recombinant protein varied in different vectors harboring heterologous genes. Trx, GST, and their fusion proteins such as GST-human parathyroid hormone (hPTH), expressed by pET32a (+), were easily auto-induced by media containing a high content of yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Despite being frequently used for protein production using T7-based E. coli expression systems in shake flask cultures [27,34], only a few investigations have considered bioreactor cultures based on auto-induction complex medium formulations [29,30,35]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being frequently used for protein production using T7-based E. coli expression systems in shake flask cultures [27,34], only a few investigations have considered bioreactor cultures based on auto-induction complex medium formulations [29,30,35]. …”
Section: Resultsmentioning
confidence: 99%
“…Cell viability and plasmid stability were evaluated by counting the final number of colonies formed [30]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol is included to (together with lactose) provide sustained growth during the induction phase (Studier 2005). In spite of the widespread use of auto-induction in shaker flask experiments, only few bioreactor cultures carried out with auto-induction media in batch (Giomarelli et al 2006; Blommel and Fox 2007a, b) or fed-batch mode (Jia et al 2011; Xu et al 2012) have been reported so far. In these studies, bioreactor media contain basically the same carbon and nitrogen sources, but the total carbon source concentration was increased by factors of approximately two (Blommel et al 2007a, b), three (Giomarelli et al 2006) or four (Xu et al 2012) in comparison to the sum of glucose, glycerol and lactose concentrations present in the original auto-induction ZYM-5052 complex formulation (Studier 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, bioreactor media contain basically the same carbon and nitrogen sources, but the total carbon source concentration was increased by factors of approximately two (Blommel et al 2007a, b), three (Giomarelli et al 2006) or four (Xu et al 2012) in comparison to the sum of glucose, glycerol and lactose concentrations present in the original auto-induction ZYM-5052 complex formulation (Studier 2005). Consequently, maximum optical densities (600 nm) in the range of ~ 20 to 40 (Giomarelli et al 2006; Blommel et al 2007a, b; Jia et al 2011) were reported for batch experiments and of 140 for fed-batch cultures (Xu et al 2012). Nevertheless, none of these studies aimed to compare induction strategies.…”
Section: Introductionmentioning
confidence: 99%